How do you simplify (3a^2b) /(5ac) x (10c) /(6ab) given that A, B, C does not equal to 0?
2 answers:
Answer:
Step-by-step explanation:
- (3a²b) /(5ac) x (10c) /(6ab) =
- (3ab)/(5c) × (5c)/(3ab)
- 1
Answer:
solution given:
(3a^2b) /(5ac) x (10c) /(6ab)
![\frac{3a {}^{2}b }{5ac} \times \frac{10c}{6ab} \\ \frac{3ab \times 10c}{5c \times 6ab} \\ \frac{2}{2} \\ 1](https://tex.z-dn.net/?f=%20%20%5Cfrac%7B3a%20%7B%7D%5E%7B2%7Db%20%7D%7B5ac%7D%20%20%5Ctimes%20%20%5Cfrac%7B10c%7D%7B6ab%7D%20%20%5C%5C%20%20%5Cfrac%7B3ab%20%5Ctimes%2010c%7D%7B5c%20%5Ctimes%206ab%7D%20%20%5C%5C%20%20%5Cfrac%7B2%7D%7B2%7D%20%20%5C%5C%201)
1 is your answer
You might be interested in
Answer:
Scenario A: Survey
Scenario B: Observational Studies
Scenario C: Experiment
Scenario D: Survey
If it not the answer you can correct me
It’s not a good idea to beg
C²=A²+B²
C²= 7² + 24²
C²= 49 + 576
C²= 625
C=√625
C=25
Answer:
x = 100
Step-by-step explanation: